Effect of bran particle size on stool weight. Issue 1 (January 1978) - Brodribb, A J; Groves, C
Abstract : The increase in stool weight after feeding 20 g (dry weight) of bran daily was measured when this was of large particle size and after milling to small particle size. Twenty-eight investigations were carried out in 21 normal subjects. With coarse bran, stool weight was significantly greater than with the fine bran (mean 219.4 g/d coarse bran, 199-0 g/d fine bran: difference 20.4 g SE +/-6.4, P less than 00.1). The coarse bran also had a greater water-holding capacity (7.3 g water/g coarse bran, 3.9 water/g fine bran). Coarse bran was 2 1/2 times the volume of fine gran for a given weight and more fine bran will, therefore, be taken when bran is prescribed by the spoonful.